2016
DOI: 10.1111/sms.12750
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for and cross‐validation of time to exhaustion on a modified Balke protocol in Norwegian men and women

Abstract: The aims of the present study were to provide reference values for time to exhaustion (TTE) on a modified Balke treadmill protocol, and to perform a cross-validation of TTE as a measure of maximal oxygen consumption (VO ), in Norwegian men and women 20-85 years of age. Reference values for TTE were derived from a national sample of 765 subjects. An additional sample of 119 subjects was included in the cross-validation (total n = 884), where prediction equations for VO was established. A decline in TTE was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…Given the inherent variation among often small and homogeneous samples from which equations are derived and tested, measurement error in the determination of VO 2peak, and variation in execution of protocols, biased predictions are expected. However, the amount of bias in these studies (± approximately 0‐8 mL/kg/min) is rather similar to the bias previously found among test centers in a multisite study and biases found in the 20 cross‐validations performed in the current study (± approximately 0‐5 mL/kg/min), relying on more similar methodology. These findings clearly show that prediction of VO 2peak should be performed with caution.…”
Section: Discussionmentioning
confidence: 51%
“…Given the inherent variation among often small and homogeneous samples from which equations are derived and tested, measurement error in the determination of VO 2peak, and variation in execution of protocols, biased predictions are expected. However, the amount of bias in these studies (± approximately 0‐8 mL/kg/min) is rather similar to the bias previously found among test centers in a multisite study and biases found in the 20 cross‐validations performed in the current study (± approximately 0‐5 mL/kg/min), relying on more similar methodology. These findings clearly show that prediction of VO 2peak should be performed with caution.…”
Section: Discussionmentioning
confidence: 51%
“…Aerobic fitness was assessed by a standardised submaximal treadmill walking protocol, modified from the maximal Balke protocol 27 to suit participants with various chronic conditions. After a 1-7 min familiarisation on a flat treadmill, participants walked with a progressive increase in inclination every minute from 0% to 12% at 4 km/hour.…”
Section: Aerobic Fitnessmentioning
confidence: 99%
“…Hence, most evidence linking physical fitness to health, such as the Cooper Center Longitudinal Study, [23][24][25] is based on time to exhaustion or maximal load on graded exercise protocols. In a recent study by Aadland, 26 time to exhaustion obtained from a treadmill-protocol in a sample of Norwegian men and women (N ¼ 884) was crossvalidated with VO2-max and confirmed to be a feasible and good measure of aerobic fitness in adults. In a similar study by Andersen, 27 maximal power output (watts) from a progressive cycle ergometer test in a sample of Danish men and women (N ¼ 535) was cross-validated with VO2-max measurements and confirmed to be a good alternative to VO2-max testing.…”
Section: Estimation Of Physical Fitnessmentioning
confidence: 93%